2007
DOI: 10.1007/bf03245968
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of techniques for the extraction of the hypotensive drugs geniposidic acid and geniposide from Eucommia ulmoides

Abstract: The extraction of geniposidic acid and geniposide from Eucommia ulmoides was carried out by Soxhlet extraction, enzyme-assisted aqueous extraction, semi-bionic extraction and supercritical fluid extraction techniques and the extracts were analyzed by high performance liquid chromatography. The results showed that the best methods for extraction of geniposidic acid and geniposide are enzyme-assisted aqueous extraction and semi-bionic extraction. Compared with various extraction methods, the semi-bionic extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…At present, there is a renewed interest in developing new processes based on the use of different variables like temperature, solvent modifiers, and material ratio for the extraction of low molecular weight components that may be environmentally friendly and benign. Previous research documentation authenticates that temperature-assisted, enzyme-assisted, supercritical-fluid-based, and semibionic-based extractions are superior over conventional soxhlet-mediated extraction [ 14 ]. It is quite complex to predict the suitable experimental conditions for a given separation task, and therefore good experimental design becomes significantly important.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is a renewed interest in developing new processes based on the use of different variables like temperature, solvent modifiers, and material ratio for the extraction of low molecular weight components that may be environmentally friendly and benign. Previous research documentation authenticates that temperature-assisted, enzyme-assisted, supercritical-fluid-based, and semibionic-based extractions are superior over conventional soxhlet-mediated extraction [ 14 ]. It is quite complex to predict the suitable experimental conditions for a given separation task, and therefore good experimental design becomes significantly important.…”
Section: Introductionmentioning
confidence: 99%
“…Although we found geniposide in the extract of B5, it could not be proven that geniposide indeed existed in the extract just based on molecular mass. Other methods must be used to obtain further conWrmation, for geniposide has anti-inXammatory activity, and it was found to be the main hypotensive compound in Eucommia ulmoides Oliver [24]. Therefore, it is highly likely that the strain B5 could produce the bioactive component, chlorogenic acid, just like its host, Eucommia ulmoides Oliver, does.…”
Section: Discussionmentioning
confidence: 96%
“…The principal components are geniposidic acid and chlorogenic acid [9,10,14,18]. Nowadays, chlorogenic acid is widely used for its antimicrobial, anti-inXammatory, antioxidant, anticancer, and anti-hepatitis B virus activities [3,13,20,23,24]. Chlorogenic acid has now been oYcially recorded in the National Pharmacopoeia of China [2].…”
Section: Introductionmentioning
confidence: 99%
“…indicated that the principal components of E. ulmoides Oliver. were geniposidic acid and chlorogenic acid, moreover, chlorogenic acid was widely used for its antimicrobial, anti-inxammatory, antioxidant, anticancer, and anti-hepatitis B virus activities (Riitta et al, 2005;Wu et al, 2007). Therefore, the next goal is to isolate and purify the acetyl acetate extract in order to confirm whether chlorogenic acid exists in the acetyl acetate extract or obtain other compounds with antifungal activities.…”
Section: Discussionmentioning
confidence: 99%